MoSe2 / SnSe2 composite nanosheet as well as preparation method and application thereof
The solution phase synthesis method is used to synthesize MoSe2/SnSe2 composite nanosheets in a short time in low temperature and short time, solving the problem of high-temperature and long-term synthesis of TMDCs heterostructures in the prior art, and achieving the preparation of high-quality nanosheets and excellent photoelectric properties.
Patent Information
- Application Number
- CN202510045176.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-10
AI Technical Summary
In the prior art, the synthesis of heterostructures of transition metal dichalcogenides (TMDCs) requires high reaction temperature and long time, and the operating conditions are complex and difficult to regulate.
By using the solution phase synthesis method, the solution A is formed by mixing the tin source, the selenium source and the solvent, and the dissolving solution B is formed by mixing the molybdenum source and the selenium source and the solvent. The reaction is carried out in the liquid phase system to form the MoSe2/SnSe2 composite nanosheets.
The successful synthesis of MoSe2/SnSe2 composite nanosheets at lower temperatures and in a short time reduces the difficulty and cost of synthesis, and improves the conductivity and photoelectric response performance of the nanostructures.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor materials, and specifically relates to a MoSe2 / SnSe2 composite nanosheet and a preparation method and application thereof. Background Art
[0002] Transition metal dichalcogenides (TMDCs) have widespread technological applications in optoelectronic devices such as photovoltaic cells, photodetectors, field-effect transistors, etc. The heterostructures of transition metal dichalcogenides can easily achieve strong built-in fields, promote separation of photogenerated carriers and suppress dark current noise, thus achieving high detectivity and high response speed.
[0003] It has been reported that SnSe2 has an indirect band gap of about 0.9 eV and SnSe2 crystal has a band gap of 8.6 cm at room temperature. 2 ·V -1 ·s -1 The high carrier mobility of MoSe2, which is higher than many other reported two-dimensional materials, makes it a good candidate for use as a wide-range photodetector. In addition, MoSe2 is a typical transition metal dichalcogenide (TMDCs) with a direct band gap of about 1.5 eV, which has potential value in the field of broadband photodetection.
[0004] At present, most studies on TMDCs heterostructures are carried out through gas phase reaction transfer processes. Gas phase reactions such as chemical vapor deposition (CVD) have been used for the scalable synthesis of high-quality atomic-thick van der Waals heterostructures. However, the high reaction temperature required for gas phase reactions and the difficult-to-control reaction kinetics limit the synthesis of TMDCs heterostructures. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a MoSe2 / SnSe2 composite nanosheet and a preparation method and application thereof. The preparation method can realize the preparation of high-quality MoSe2 / SnSe2 composite nanosheets, and effectively reduce the synthesis temperature and synthesis time, and can also reduce the difficulty of operating conditions and preparation costs.
[0006] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a MoSe2 / SnSe2 composite nanosheet, comprising the following steps: S1: mixing a tin source, a selenium source and a solvent to obtain a dissolving solution A; mixing a molybdenum source, a selenium source and a solvent to obtain a dissolving solution B; The tin source is selected from tetraphenyltin; S2: In a liquid phase system including a solvent, a first reaction is carried out after adding a dissolving liquid A, and then a second reaction is carried out after adding a dissolving liquid B to form a MoSe2 / SnSe2 composite nanosheet.
[0007] Preferably, the adding of the dissolving liquid A is carried out at 260-300°C.
[0008] Preferably, the first reaction time is 5 to 10 min.
[0009] Preferably, the selenium source is selected from dibenzyl diselenide.
[0010] Preferably, the molybdenum source is selected from molybdenum acetylacetonate.
[0011] In the present invention, the selection of the molybdenum source will affect the morphology of the final product. Therefore, the present invention selects molybdenum acetylacetonate as the molybdenum source after screening.
[0012] Preferably, the solvent is selected from any one or more of oleylamine, oleic acid or octadecene.
[0013] Preferably, the molar ratio of the tin source to the selenium source is 0.050:(0.050-0.010); the dosage ratio of the tin source to the solvent is 0.05 mmol:(1-3) mL.
[0014] Preferably, the molar ratio of the molybdenum source to the selenium source is 0.050:(0.050~0.075); the dosage ratio of the molybdenum source to the solvent is 0.05 mmol:(1~3)mL.
[0015] Preferably, the mixing of the dissolving solution A and the dissolving solution B in step S1 is performed under ultrasonic conditions.
[0016] Preferably, the power of the ultrasound is 150-200 W, and the time is 5-10 min.
[0017] Preferably, after the mixing of the solution A and the solution B in step S1 is completed, the system is heated to 110-150° C. and kept warm for 15-40 min under protective gas conditions.
[0018] Preferably, the first reaction and the second reaction are carried out under a protective atmosphere.
[0019] Preferably, the temperature of the second reaction is 260-300° C., and the time is 5-35 min.
[0020] Preferably, after the second reaction is completed, cooling, washing and drying are further included.
[0021] In a second aspect, the present invention provides a MoSe2 / SnSe2 composite nanosheet prepared by the above-mentioned preparation method, wherein the composite nanosheet has a hexagonal sheet morphology; the surface of the hexagonal sheet is covered with scaly sheets.
[0022] Preferably, the diameter of the hexagonal flakes is 400-700 nm.
[0023] In a third aspect, the present invention further provides an infrared light detection device, which comprises the MoSe2 / SnSe2 composite nanosheets prepared by the above preparation method.
[0024] Preferably, the infrared light detection device further includes graphene, a silicon wafer, a metal electrode and a circuit board.
[0025] Compared with the prior art, the present invention has the following beneficial effects: The present invention successfully synthesizes MoSe2 / SnSe2 composite nanosheets in a short time at a relatively low reaction temperature. Compared with heterostructures such as vapor deposition that require a reaction temperature of 80 h at a temperature above 900°C, the synthesis of nanocomposite heterostructures requires a low reaction temperature, a short reaction time, and convenient and simple operation. In addition, the MoSe2 / SnSe2 composite nanosheets prepared by the present invention are in the form of hexagonal sheets coated with scales, and the morphology is different from the nanosheets of the monomer SnSe2 and the nanoflowers of MoSe2. According to the test, the band gap of the composite nanosheets in the form of hexagonal sheets is 0.88 eV, which is different from the band gap (0.71 eV) of the SnSe2 monomer and the band gap (1.47 eV) of the MoSe2 monomer prepared by the method. The reason for the difference is that the formation of the SnSe2 and MoSe2 composite nanosheets flattens the band gap and improves the conductivity of the nanostructure.
[0026] The present invention uses Keithley 2400 semiconductor performance analysis system to test a near-infrared optoelectronic device composed of MoSe2 / SnSe2 composite nanosheets, graphene, silicon wafers, metal electrodes and circuit boards. The results show that the device has good photoelectric response performance, especially the response to light with a wavelength of 808 nm. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM test image of the MoSe2 / SnSe2 composite nanosheet obtained in Example 1; Figure 2 TEM test image of MoSe2 / SnSe2 composite nanosheets obtained in Example 1; Figure 3 The high-angle annular dark field image (HAADF-STEM) of the MoSe2 / SnSe2 composite nanosheet obtained in Example 1 and the mapping diagram of Sn, Mo, and Se elements; wherein, Figure 3 a is a high-angle annular dark field image. Figure 3 b is the Mapping diagram of Mo element, Figure 3 c is the Mapping diagram of Sn element, Figure 3 d is the Mapping diagram of Se element; Figure 4 XRD patterns of the MoSe2 / SnSe2 composite nanosheets obtained in Example 1 and the SnSe2 and MoSe2 obtained in Comparative Examples 1 and 2; Figure 5 This is the XPS graph of the MoSe2 / SnSe2 composite nanosheet obtained in Example 1; wherein, Figure 5 a is the XPS total spectrum of MoSe2 / SnSe2 nanomaterials, Figure 5 b is the spectrum of Sn3d, Figure 5 c is the spectrum of Mo3d, Figure 5 d is the spectrum of Se3d Figure 6 The characteristic absorption spectrum of the MoSe2 / SnSe2 composite nanosheet obtained in Example 1 and the band gap diagram obtained by fitting the characteristic absorption spectrum; in, Figure 6 a is the characteristic absorption spectrum of MoSe2 / SnSe2 composite nanosheets obtained in Example 1; Figure 6 b is the band gap diagram obtained by fitting the characteristic absorption spectrum; Figure 7 This is an optical photograph of the photodetector device for performance testing prepared in Example 1 of the present invention; Figure 8 The MoSe2 / SnSe2 composite nanosheet photodetector device prepared in Example 1 of the present invention is shown in Figure 1 under the same light intensity and different wavelengths. IV curve; Fig. 9 The MoSe2 / SnSe2 composite nanosheet photodetector device prepared in Example 1 of the present invention is subjected to light of 808 nm wavelength at different intensities. IV curve; Fig.10 Transmission electron microscope (TEM) images of MoSe2 / SnSe2 composite nanosheets with different MoSe2 / SnSe2 ratios obtained in Example 2; in Fig.10 a~10d are TEM of MoSe2:SnSe2=2:1, 1:1, 1:2, 1:4 composite nanosheets, respectively; Fig.11 X-ray diffraction (XRD) patterns of MoSe2 / SnSe2 composite nanosheets with different composite ratios obtained in Example 2; Fig.12The transmission electron microscope (TEM) test images of MoSe2 / SnSe2 composite nanosheets with different reaction times obtained in Example 3; in, Fig.12 a is the TEM image after 5 min reaction. Fig.12 b is the TEM image with a reaction time of 40 min; Fig.13 TEM test images of SnSe2 monomer and MoSe2 monomer materials obtained in Comparative Examples 1 and 2; wherein, Fig.13 a is the TEM test image of the single SnSe2 nanosheet. Fig.13 b is the TEM test image of the monomer MoSe2 nanoflower; Fig.14 Characteristic absorption spectra of SnSe2 and MoSe2 obtained in Comparative Examples 1 and 2 and band gap diagrams obtained by fitting the characteristic absorption spectra; in, Fig.14 a is the characteristic absorption spectrum of SnSe2 obtained in Comparative Example 1, Fig.14 b is the band gap diagram obtained by fitting the characteristic absorption spectrum of SnSe2. Fig.14 c is the characteristic absorption spectrum of MoSe2 obtained in Comparative Example 2, Fig.14 d is the band gap diagram obtained by fitting the characteristic absorption spectrum of MoSe2; Fig.15 TEM test images of SnSe2 monomer materials and composites obtained in Comparative Examples 3, 4, 5, and 6; wherein, Fig.15 a is a TEM test image of SnSe2 nanobelts obtained by reaction with crystalline tin tetrachloride as tin source; Fig.15 b is the TEM test image of SnSe2 cube obtained by reaction with tin dioxide as tin source; Fig.15 c is a TEM test image of the complex formed by SnSe2 nanobelts and MoSe2 obtained by the reaction with crystalline tin tetrachloride as the tin source; Fig.15 d is the TEM test image of SnSe2 nanobelts composited with MoSe2 obtained by reaction with tin dioxide as tin source; Fig.16 This is the XRD diagram of the SnSe2 monomer material obtained in Comparative Examples 3 and 4. DETAILED DESCRIPTION
[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In view of the fact that in the prior art, TMDCs heterostructures are mostly prepared by gas phase reaction, which has the problems of being difficult to control and having high reaction temperature, the present invention provides a method for preparing MoSe2 / SnSe2 composite nanosheets, comprising the following steps: S1: mixing a tin source, a selenium source and a solvent to obtain a dissolving solution A; mixing a molybdenum source, a selenium source and a solvent to obtain a dissolving solution B; S2: In a liquid phase system including a solvent, a first reaction is carried out after adding a dissolving liquid A, and then a second reaction is carried out after adding a dissolving liquid B to form a MoSe2 / SnSe2 composite nanosheet.
[0030] In the present invention, firstly, a tin source, a selenium source and a solvent are mixed to obtain a dissolving solution A; and a molybdenum source, a selenium source and a solvent are mixed to obtain a dissolving solution B. The steps of obtaining the dissolving solution A and the dissolving solution B are not limited in order.
[0031] The present invention has been studied and found that the selection of tin source will affect the final MoSe2 / SnSe2 composite nanosheets. Therefore, the present invention has selected and preferably selected an organic tin source, and more preferably tetraphenyltin as the tin source.
[0032] In the present invention, the selenium source is selected from dibenzyl diselenide; the molybdenum source is preferably selected from an organic molybdenum source, more preferably molybdenum acetylacetonate; the solvent is selected from any one or more of oleylamine, oleic acid or octadecene, preferably oleylamine.
[0033] In some embodiments of the present invention, the molar ratio of the tin source to the selenium source is preferably 0.050:(0.050~0.010), preferably 0.050:(0.070~0.010); the dosage ratio of the tin source to the solvent is 0.05 mmol:(1~3) mL, preferably 0.05 mmol:(1~2) mL, and the tin source, the selenium source and the solvent are mixed to obtain a dissolving solution A.
[0034] In some embodiments of the present invention, the molar ratio of the molybdenum source to the selenium source is preferably 0.050:(0.050~0.075), preferably 0.050:(0.050~0.065); the amount ratio of the molybdenum source to the solvent is 0.05 mmol:(1~3) mL, preferably 0.05 mmol:(1~2) mL, and the molybdenum source, selenium source and solvent are mixed to obtain a dissolving solution B.
[0035] In some preferred embodiments of the present invention, the mixing of the dissolving solution A and the dissolving solution B in step S1 is performed under ultrasonic conditions, specifically: The tin source, the selenium source and the solvent are ultrasonically mixed to obtain a dissolving solution A; the molybdenum source, the selenium source and the solvent are ultrasonically mixed to obtain a dissolving solution B.
[0036] The conditions for the ultrasonic mixing are preferably: power 150-200 W, more preferably 190 W; time 5-10 min, more preferably 5 min; in some embodiments of the present invention, the ultrasonic power is 190 W; and the ultrasonic time is 5 min.
[0037] In some specific embodiments of the present invention, the step of obtaining solution A and solution B is preferably: 0.050 mmol (0.0214 g) of tetraphenyltin, 0.10 mmol (0.0340 g) of dibenzyl diselenide and 1.0 mL of oleylamine were weighed and placed in a 10 mL centrifuge tube for ultrasonic dissolution at an ultrasonic power of 190 W for 5 min to obtain solution A. 0.050 mmol (0.0163 g) of molybdenum acetylacetonate, 0.050 mmol (0.0170 g) of dibenzyl diselenide and 1.0 mL of oleylamine were weighed and placed in a 10 mL centrifuge tube for ultrasonic dissolution at an ultrasonic power of 190 W for 5 min to obtain solution B.
[0038] According to the present invention, after the dissolving solution A and the dissolving solution B are obtained, a liquid phase system containing a solvent is provided.
[0039] In some embodiments of the present invention, the liquid phase system containing the solvent is preferably heated to 110-150°C under protective gas conditions and kept warm for 15-40 min to remove moisture and low-boiling impurities. In some embodiments of the present invention, the temperature is raised to 120°C and kept warm for 30 min. The present invention has no particular limitation on the type of the protective gas, and it can be a conventional protective gas well known to those skilled in the art, such as nitrogen or argon.
[0040] In some specific preferred embodiments of the present invention, oleylamine is preferably added to a three-necked flask, and the system temperature is raised to 110-150°C and kept for 15-40 min, more preferably kept at 120-140°C for 20-30 min, under the stirring of a high-temperature stirring magnetic rod and in a reaction atmosphere of a high-purity protective gas, to remove moisture and low-boiling impurities. The rotation speed of the high-temperature stirring magnetic rod is 300-500 rpm, more preferably 400 rpm.
[0041] Then, according to the present invention, in a liquid phase system containing a solvent, a dissolving liquid A is added and a first reaction is carried out. At this time, preferably, the dissolving liquid A is added according to a ratio of the solvent to the tin source in the dissolving liquid A of (5~10) mL: 0.05 mmol, preferably 0.05 mmol: 5mL. Wherein, the adding of the dissolving liquid A is preferably carried out at 260~300°C, more preferably at 270~290°C, and more preferably at 280°C. That is, it is preferred that the liquid phase system containing a solvent is heated to 260~300°C, and then the dissolving liquid A is added to carry out the first reaction. The reaction is preferably carried out at 260~300°C for 5~10 min.
[0042] After the first reaction is completed, according to the present invention, it is preferred to add a dissolving solution B for a second reaction to form MoSe2 / SnSe2 composite nanosheets. The addition of the dissolving solution B is preferably carried out at a temperature of 260-300°C, more preferably 270-290°C. In some embodiments of the present invention, the dissolving solution B is added at 280°C. The reaction time is preferably 5-35 min, more preferably 25 min, at which time MoSe2 / SnSe2 composite nanosheets can be obtained; the protective gas atmosphere is maintained until the reaction is completed, cooled to room temperature, and then the product is taken out.
[0043] It should be noted that the dissolving solution A and the dissolving solution B are added in the following manner: the dissolving solution A and the dissolving solution B are placed in a syringe and added into the liquid phase system in the form of injection.
[0044] In the present invention, the order in which the dissolving solution A and the dissolving solution B are added to the liquid phase system is very important. If the dissolving solution B is added first and then the dissolving solution A is added, the target morphology of the MoSe2 / SnSe2 composite nanosheets cannot be obtained.
[0045] In some preferred embodiments of the present invention, after the reaction is completed, the following post-treatment is preferably performed: cooling, washing and drying. The cooling is preferably to cool naturally to room temperature under a protective gas atmosphere after the reaction is stopped. The above product is centrifuged at 8000-10000 rpm for 2-5 min in a centrifuge, the liquid is discarded to retain the black precipitate, and it is repeatedly washed 2-3 times with anhydrous ethanol and / or n-hexane. After the above washing, the obtained black solid is dried. The drying is preferably vacuum drying; the drying temperature is preferably 30-60°C, and the drying is 5-15 min to obtain MoSe2 / SnSe2 composite nanosheets. According to SEM characterization, the obtained MoSe2 / SnSe2 composite nanosheets are hexagonal nanosheets, and the surface of the hexagonal sheets is distributed with scaly small sheets. The diameter of the hexagonal sheet is 400-700 nm, preferably about 600 nm.
[0046] The preparation method provided by the present invention is a solution phase synthesis method, which uses a tin source, a molybdenum source and a selenium source as precursors, reacts in a liquid phase reaction medium, and obtains MoSe2 / SnSe2 composite nanosheets through a two-step hot injection synthesis, which greatly reduces the reaction temperature and reaction time, is simple to operate, convenient and easy to operate, and easy to control.
[0047] After testing, the band gap of the MoSe2 / SnSe2 hexagonal composite nanosheet provided by the present invention is 0.88 eV, which is different from the band gap of the SnSe2 monomer (0.71 eV) and the band gap of the MoSe2 monomer (1.47 eV). The reason for the difference is that the formation of the SnSe2 and MoSe2 composite nanosheets flattens the band gap and improves the conductivity of the nanostructure.
[0048] The present invention also provides an infrared light detection device, which includes the MoSe2 / SnSe2 composite nanosheet involved in the above technical solution. Generally, the infrared light detection device also includes graphene, a silicon wafer, a metal electrode and a circuit board.
[0049] In some embodiments of the present invention, the infrared light detection device is composed of MoSe2 / SnSe2 composite nanosheets, graphene, silicon wafer, metal electrodes and circuit boards, etc. The MoSe2 / SnSe2 composite nanosheets are in contact with graphene and silicon wafers, and the silicon wafer and graphene are respectively connected to metal electrodes; the metal electrodes are connected to the circuit board.
[0050] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products. Example 1
[0051] This embodiment provides a MoSe2 / SnSe2 composite nanosheet, and the preparation method thereof is as follows: S1. Add 5 mL of oleylamine into a 100 mL three-necked flask. Under the stirring of a high-temperature stirring magnet, raise the temperature to 120°C in a reaction atmosphere of high-purity argon and maintain for 30 min to remove moisture and low-boiling impurities. S2. Weigh 0.050 mmol (0.0214 g) of tetraphenyltin, 0.10 mmol (0.0340 g) of dibenzyl diselenide and 1.0 mL of oleylamine and place them in a 10 mL centrifuge tube for ultrasonic dissolution at an ultrasonic power of 190 W for 5 min to obtain solution A. S3, weigh 0.050 mmol (0.0163 g) of molybdenum acetylacetonate, 0.050 mmol (0.0170 g) of dibenzyl diselenide and 1.0 mL of oleylamine, place them in a 10 mL centrifuge tube and dissolve them by ultrasonication at a power of 190 W for 5 min to obtain solution B; S4, the mixed solution in the three-necked flask obtained in step S1 was heated to 280°C, and under this condition, the solution A obtained in step S2 was quickly injected into the three-necked flask, and the reaction solution immediately turned black; after reacting for 5 minutes, the solution B obtained in step S3 was quickly injected into the three-necked flask, and then reacted for another 25 minutes. After the reaction was completed, it was naturally cooled to room temperature in a high-purity argon atmosphere, centrifuged, and then repeatedly washed with anhydrous ethanol and n-hexane, and finally centrifuged and placed in a vacuum drying oven to obtain MoSe2 / SnSe2 composite nanosheets.
[0052] Figure 1 This is a scanning electron microscope (SEM) test image of the MoSe2 / SnSe2 composite nanosheet obtained in Example 1. It can be seen that the nanosheet is a hexagonal sheet with a diameter of about 600 nm, as shown by the yellow dotted line in the figure; there are scaly small pieces distributed on the surface of the hexagonal sheet (such as the blue area).
[0053] Figure 2 This is a transmission electron microscope (TEM) test image of the MoSe2 / SnSe2 composite nanosheet obtained in Example 1; it more clearly shows the hexagonal sheet structure with scaly flakes on the surface, forming a foggy outer layer.
[0054] Figure 3 The high-angle annular dark field image (HAADF-STEM) of the MoSe2 / SnSe2 composite nanosheet obtained in Example 1 and the mapping diagram of Sn, Mo, and Se elements; wherein, Figure 3 a is a high-angle annular dark field image. Figure 3 b is the Mapping diagram of Mo element, Figure 3 c is the Mapping diagram of Sn element, Figure 3 d is the mapping diagram of Se element; it can be seen that Mo element is distributed in the outer layer of the hexagonal sheet and along the scale texture; Sn element is mainly distributed in the center of the hexagonal sheet, showing a hexagonal distribution, and is not distributed in the extended scale texture; Se element is distributed in the entire morphology structure.
[0055] Figure 4The X-ray diffraction (XRD) patterns of the MoSe2 / SnSe2 composite nanosheets obtained in Example 1 and the SnSe2 and MoSe2 obtained in subsequent Comparative Examples 1 and 2 are shown. It can be seen that the diffraction peaks at 14.2°, 28.9°, 30.9°, 39.8°, 44.1°, 47.6°, 49.6°, 52.5° and 60.3° correspond to the (001), (002), (011), (012), (003), (110), (111), (103) and (004) crystal planes of the SnSe2 standard card (JCPDS card, 01−089−2939). The diffraction peaks at 31.1°, 37.7° and 55.8° correspond to the (100), (103) and (110) crystal planes of the MoSe2 standard card (JCPDS card, 01−087−2419). Due to the poor crystallinity of MoSe2, the diffraction peak intensity is much smaller than that of SnSe2, so the diffraction peak of MoSe2 is not obvious in the diffraction pattern of the composite nanosheets.
[0056] Figure 5 This is an X-ray photoelectron spectroscopy (XPS) diagram of the MoSe2 / SnSe2 composite nanosheet obtained in Example 1; wherein, Figure 5 a is the XPS total spectrum of MoSe2 / SnSe2 composite nanosheets, Figure 5 b is the 3d spectrum of Sn, Sn 4+ 3D 5 / 2 and 3D 3 / 2 The signal peaks of α shifted from 485.8 eV and 494.3 eV to 486.4 eV and 494.8 eV. Figure 5 c is the 3d spectrum of Mo, 5 / 2 and 3D 3 / 2 The signal peaks of the SnSe2 nanosheets shifted from the low-energy region of 229.1 eV and 232.2 eV to 228.8 eV and 231.9 eV, which indicates that the Mo element on the surface of the composite nanosheets obtained electrons through the interface surface of the substrate SnSe2 nanosheets, which also means that a coupling interface is established between SnSe2 and MoSe2.
[0057] Figure 6 The characteristic absorption spectrum of MoSe2 / SnSe2 composite nanosheets obtained in Example 1 ( Figure 6 a) and the band gap diagram obtained by fitting the absorption spectrum ( Figure 6 b) The band gap of the product of this example is 0.88 eV.
[0058] Figure 7 This is an optical photograph of the photodetector device prepared in Example 1 for performance testing.
[0059] Figure 8The MoSe2 / SnSe2 composite nanosheet photodetector device prepared in Example 1 under the same light intensity and different wavelengths IV Graphs; Fig. 9 The MoSe2 / SnSe2 composite nanosheet photodetector device prepared in Example 1 of the present invention is subjected to light of 808 nm wavelength at different intensities. IV Graph.
[0060] Depend on Figures 8 and 9 It can be seen that in addition to the wide spectral response, under a fixed light intensity, the photocurrent of the device increases with the increase of the wavelength of the incident light, until it reaches the highest at a wavelength of 808 nm, and then begins to decline. This shows that the device has a strong selectivity for 808 nm wavelength light. By changing the light intensity (from 5 W / cm 2 Up to 50 mW / cm 2 ), it can be seen that the photocurrent increases with the increase of light intensity. Example 2
[0061] Compared with Example 1, the molybdenum acetylacetonate in the dissolving solution B in step S3 is changed to 2 times, 0.5 times, and 0.25 times of the original amount to change the amount of MoSe2 in the composite nanosheet, thereby changing the composite ratio of the two monomers in the composite nanosheet. At the same time, the amount of dibenzyl diselenide in the dissolving solution B changes accordingly with the change in the amount of molybdenum acetylacetonate. The remaining steps and parameters are consistent with Example 1.
[0062] Fig.10 The transmission electron microscope (TEM) test images of MoSe2 / SnSe2 composite nanosheets with different MoSe2 / SnSe2 ratios obtained in Example 2; Fig.10 a~10d are TEM images of MoSe2:SnSe2=2:1, 1:1, 1:2, 1:4 composite nanosheets, respectively. High-quality MoSe2 / SnSe2 composite nanosheets can be obtained within this composite range. As the amount of composite MoSe2 decreases, the foggy outer layer formed by MoSe2 scaly nanosheets on the composite surface becomes less.
[0063] Fig.11 The X-ray diffraction (XRD) patterns of MoSe2 / SnSe2 composite nanosheets with different composite ratios obtained in Example 2; it can be seen that with the increase in the amount of MoSe2 composite, the diffraction peak of XRD is closer to the monomer MoSe2. Example 3
[0064] Compared with Example 1, the second reaction time after the dissolving solution B is injected into S4 is adjusted to 5 min and 40 min respectively. The remaining parameters and steps are consistent with Example 1.
[0065] Fig.12The transmission electron microscope (TEM) test images of MoSe2 / SnSe2 composite nanosheets with different reaction times obtained in Example 3 are shown in FIG. Fig.12 a is a TEM image after 5 min of reaction. The morphology of the composite nanosheets has been basically formed, but SnSe2 nanosheets can still be observed. Fig.12 b is the TEM image when the reaction time is increased to 40 min after the injection of solvent B, and it can be observed that the composite nanosheets are broken.
[0066] Comparative Example 1 This comparative example provides a monomer SnSe2 material, and its preparation method is as follows: S1. Add 5 mL of oleylamine into a 100 mL three-necked flask. Under the stirring of a high-temperature stirring magnet, raise the temperature to 120°C in a reaction atmosphere of high-purity argon and maintain for 30 min to remove moisture and low-boiling impurities. S2. Weigh 0.050 mmol (0.0214 g) of tetraphenyltin, 0.10 mmol (0.0340 g) of dibenzyl diselenide and 1.0 mL of oleylamine and place them in a 10 mL centrifuge tube for ultrasonic dissolution at an ultrasonic power of 190 W for 5 min to obtain solution A. S3, the mixed solution in the three-necked flask obtained in step S1 was heated to 280°C, and the solution A obtained in step S2 was quickly injected into the three-necked flask under this condition, and the reaction solution immediately turned black, and the reaction was continued for 30 min. After the reaction was completed, it was naturally cooled to room temperature in a high-purity argon atmosphere, centrifuged, and then repeatedly washed with anhydrous ethanol and n-hexane, and finally centrifuged and dried in a vacuum drying oven to obtain monomer SnSe2 nanosheets.
[0067] Comparative Example 2 This comparative example provides a monomer MoSe2 material, and its preparation method is as follows: Refer to Comparative Example 1, except that step S2 is changed to: weigh 0.050 mmol (0.0163 g) of molybdenum acetylacetonate, 0.050 mmol (0.0170 g) of dibenzyl diselenide and 1.0 mL of oleylamine and place them in a 10 mL centrifuge tube for ultrasonic dissolution, the ultrasonic power is 190 W, the time is 5 min, and a dissolving solution B is obtained; in step S3, when the reaction temperature is reached, the dissolving solution B is injected, and the other parameters and steps are consistent with Comparative Example 1.
[0068] Fig.13 TEM test images of SnSe2 monomer material and MoSe2 monomer material obtained in Comparative Examples 1 and 2; wherein, Fig.13 a is the TEM test image of the monomer SnSe2 hexagonal nanosheet. The diameter of the hexagonal sheet is about 500 nm and there is no scaly texture on the surface; Fig.13b is the TEM test image of the monomer MoSe2 nanoflower, and the texture is similar to the scaly texture of the composite nanosheet.
[0069] Fig.14 Characteristic absorption spectra of SnSe2 and MoSe2 nanomaterials obtained in Comparative Examples 1 and 2 and the band gaps obtained by fitting the absorption spectra. The band gaps of the products of Comparative Examples 1 and 2 are 0.71 eV and 1.47 eV, respectively.
[0070] Comparative Example 3 S1. Add 5 mL of oleylamine into a 100 mL three-necked flask. Under the stirring of a high-temperature stirring magnet, raise the temperature to 120°C in a reaction atmosphere of high-purity argon and maintain for 30 min to remove moisture and low-boiling impurities. S2, weigh 0.01 mmol (0.0351 g) of crystalline tin tetrachloride, 0.10 mmol (0.0340 g) of dibenzyl diselenide and 1.0 mL of oleylamine, place them in a 10 mL centrifuge tube and dissolve them by ultrasonication at an ultrasonic power of 190 W for 5 min to obtain solution A; S3, the mixed solution in the three-necked flask obtained in step S1 was heated to 280°C, and the solution A obtained in step S2 was quickly injected into the three-necked flask under this condition, and the reaction solution immediately turned black and reacted for 30 min. After the reaction was completed, it was naturally cooled to room temperature in a high-purity argon atmosphere, centrifuged, and then repeatedly washed with anhydrous ethanol and n-hexane, and finally centrifuged and dried in a vacuum drying oven to obtain a monomer SnSe2 nanobelt.
[0071] Comparative Example 4 Compared with Comparative Example 3, the only difference is that 0.01 mmol of crystalline tin tetrachloride in S2 is replaced by 0.01 mmol of tin dioxide (0.0111 g), and the other parameters and steps are consistent with Comparative Example 3.
[0072] Comparative Example 5 Compared with Example 1, the only difference is that the tetraphenyltin in S2 is replaced by crystalline tin tetrachloride, and the other parameters and steps are consistent with Example 1.
[0073] Comparative Example 6 Compared with Example 1, the only difference is that tetraphenyltin in S2 is replaced by tin dioxide, and the other parameters and steps are consistent with Example 1.
[0074] The TEM test images of SnSe2 monomer materials and composites obtained in Comparative Examples 3, 4, 5, and 6 are as follows: Fig.15 As shown; among them, Fig.15 a is a TEM test image of SnSe2 nanobelts obtained by reaction with crystalline tin tetrachloride as tin source; Fig.15b is the TEM test image of SnSe2 cube obtained by reaction with tin dioxide as tin source; Fig.15 c is a TEM test image of the complex formed by SnSe2 nanobelts and MoSe2 obtained by the reaction with crystalline tin tetrachloride as the tin source; Fig.15 d is the TEM test image of SnSe2 nanobelts composited with MoSe2 obtained by reaction with tin dioxide as tin source. Fig.15 a. Fig.15 b. Fig.13 a By comparison, it is known that the SnSe2 monomers synthesized with crystalline tin tetrachloride as the tin source and tin dioxide as the tin source cannot form the same morphology as the hexagonal SnSe2 nanosheets synthesized with tetraphenyltin as the tin source; Fig.15 c and Fig.15 a. Figure 2 By comparison, the SnSe2 nanobelts obtained with crystalline tin tetrachloride as the tin source can be successfully composited with MoSe2 to obtain a composite with a different morphology from that of the SnSe2 nanobelts, but cannot be obtained as Figure 2 The obtained high-quality hexagonal composite nanosheets; Fig.15 d and Fig.15 b Comparison shows that the SnSe2 monomer obtained using tin dioxide as the tin source cannot be composited with MoSe2, and the morphology of the SnSe2 monomer obtained by the tin source is destroyed.
[0075] The XRD patterns of the SnSe2 monomer materials obtained in Comparative Examples 3 and 4 are as follows: Fig.16 Under the same conditions, SnSe2 monomer can be obtained using crystalline tin tetrachloride and tin dioxide as tin sources, but part of the tin dioxide in the latter is not completely reacted.
[0076] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing MoSe2 / SnSe2 composite nanosheets, characterized in that: The following steps are involved: S1: mixing a tin source, a selenium source and a solvent to obtain a dissolving solution A; mixing a molybdenum source, a selenium source and a solvent to obtain a dissolving solution B; The tin source is selected from tetraphenyltin; S2: In a liquid phase system including a solvent, a first reaction is carried out after adding a dissolving liquid A, and then a second reaction is carried out after adding a dissolving liquid B to form a MoSe2 / SnSe2 composite nanosheet.
2. The preparation method according to claim 1, characterized in that: The adding of the dissolving liquid A is carried out at 260-300° C.; The first reaction time is 5 to 10 min.
3. The preparation method according to claim 1 or 2, characterized in that: The selenium source is selected from dibenzyl diselenide; The molybdenum source is selected from molybdenum acetylacetonate; The solvent is selected from any one or more of oleylamine, oleic acid or octadecene.
4. The preparation method according to any one of claims 1 to 3, characterized in that The molar ratio of the tin source to the selenium source is 0.050:(0.050-0.010); the dosage ratio of the tin source to the solvent is 0.05 mmol:(1-3) mL; The molar ratio of the molybdenum source to the selenium source is 0.050:(0.050-0.075); the dosage ratio of the molybdenum source to the solvent is 0.05 mmol:(1-3) mL.
5. The preparation method according to any one of claims 1 to 4, characterized in that The mixing of the dissolving solution A and the dissolving solution B obtained in step S1 is performed under ultrasonic conditions; The power of the ultrasound is 150-200 W, and the time is 5-10 min; After the mixing of the solution A and the solution B is completed in step S1, the system is heated to 110-150° C. and kept warm for 15-40 min under protective gas conditions.
6. The preparation method according to any one of claims 1 to 5, characterized in that The reaction is carried out under a protective atmosphere; The temperature of the second reaction is 260-300°C and the time is 25-35 min; After the second reaction is completed, the steps include cooling, washing and drying.
7. The MoSe2 / SnSe2 composite nanosheet prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The composite nanosheet has a hexagonal sheet morphology; The surface of the hexagonal sheet is covered with scale-like sheets.
8. The MoSe2 / SnSe2 composite nanosheet according to claim 7, characterized in that: The diameter of the hexagonal flakes is 400-700 nm.
9. An infrared light detection device, characterized in that: The invention relates to a MoSe2 / SnSe2 composite nanosheet prepared by the preparation method according to any one of claims 1 to 6.
10. The infrared light detection device according to claim 9, characterized in that: The infrared light detection device also includes graphene, a silicon wafer, a metal electrode and a circuit board.
Citation Information
Patent Citations
Liquid-phase preparation method of cubic phase Cu2SnTe3 nanometer crystal
CN105174235A
Method for preparing polycrystalline SnSe2 material by solution method
CN109607495A
MoSe2 / Co9S8 nano-heterostructure material, and preparation method and application thereof
CN111215099A
Preparation method of MoS2 / SnSe2 / H-TiO2 heterojunction photoelectric detector
CN113097321A
Heat treatment method and heat treatment apparatus
KR1020230098523A